2016
DOI: 10.1093/mnras/stw2257
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas kinematics and line diagnostics in early-type galaxies: NGC 4710 and NGC 5866

Abstract: We present interferometric observations of CO lines ( 12 CO(1-0, 2-1) and 13 CO(1-0, 2-1)) and dense gas tracers (HCN(1-0), HCO + (1-0), HNC(1-0) and HNCO(4-3)) in two nearby edgeon barred lenticular galaxies, NGC 4710 and NGC 5866, with most of the gas concentrated in a nuclear disc and an inner ring in each galaxy. We probe the physical conditions of a two-component molecular interstellar medium in each galaxy and each kinematic component by using molecular line ratio diagnostics in three complementary ways.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 69 publications
5
28
0
Order By: Relevance
“…As revealed from Figure 5, there is degeneracy in T K due to its characteristic 'banana'-shaped ∆χ 2 r contours or inverse n (H 2 ) − T K relationship ( [25,37]; see also appendix C of [15]). The PDF of the kinetic temperature T K also shows a single-peaked distribution peaked at 20 K where the χ 2 result meets with the peak, followed by a steady decrease.…”
Section: Modeling Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As revealed from Figure 5, there is degeneracy in T K due to its characteristic 'banana'-shaped ∆χ 2 r contours or inverse n (H 2 ) − T K relationship ( [25,37]; see also appendix C of [15]). The PDF of the kinetic temperature T K also shows a single-peaked distribution peaked at 20 K where the χ 2 result meets with the peak, followed by a steady decrease.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…We compare our best-fitting results (listed in Table 5) to that of literature studies done for the center and along the disc of one spiral and one ETG using similar lines and the same methods. Molecular gas properties along the disc of the spiral galaxy NGC 6946 and ETG NGC 4710 [25][26][27]37] were also studied using the LVG approximation. We found that n (H 2 ) is to be higher in the center of NGC 2903 compared to that found in most of the regions studied in the arms of NGC 6946 [25] and in the center of NGC 6946 [26,27].…”
Section: Modeling Resultsmentioning
confidence: 99%
See 3 more Smart Citations